ASSESSING EMOTIONAL INTELLIGENCE: A LITERATURE REVIEW - Hudson, Sharon (Acta Scientiae et Intellectus, 2024)
The purpose of the literature review is to examine the empirical evidence associated with emotional intelligence (EI) measurement. A search of the periodical database PsychINFO and a Google Internet search produced studies associated with ability model, mixed model, and trait model approaches to assessment. The key search term ‘assessing emotional intelligence’ was not limited by date of publication. The emotional intelligence tests selected for review include the Bar-On Emotional Quotient Inventory, Emotional & Social Competence Inventory, Emotional & Social competence Inventory – University Edition, Genos Emotional Intelligence Inventory, Group Emotional Competency Inventory, Mayer-Salovey-Caruso EI Test, Schutte Self-Report Emotional Intelligence Scale, Trait Emotional Intelligence Questionnaire, Work Group Emotional Intelligence Profile, and Wong and Law Emotional Intelligence Scale. Emotional intelligence testing is applicable to both business and academic related performance to measure leadership ability and assess behavior. Theory links high emotional intelligence to enhanced performance, better outcomes, and improved mental status. Criticism of emotional intelligence testing is linked to consensus-based assessment and self-report measures. The complex constructs of emotional intelligence require a multifaceted approach of more than one measure and consideration of personality measures.